2023
DOI: 10.3389/fcimb.2023.1142140
|View full text |Cite
|
Sign up to set email alerts
|

Causal effects of gut microbiota on the risk of chronic kidney disease: a Mendelian randomization study

Abstract: BackgroundPrevious studies have reported that gut microbiota is associated with an increased risk of chronic kidney disease (CKD) progression. However, whether gut microbiota has a causal effect on the development of CKD has not been revealed. Thus, we aimed to analyze the potential causal effect of gut microbiota on the risk of CKD using mendelian randomization (MR) study.Materials and MethodsIndependent single nucleotide polymorphisms closely associated with 196 gut bacterial taxa (N = 18340) were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 63 publications
0
25
0
Order By: Relevance
“…Our study found that out of 211 classes of gut microbiota, 6 classes of gut microbes were causally associated with increased risk of HF, namely genus Eubacterium eligens group, class Negativicutes, genus Eubacterium oxidoreducens group, genus Flavonifractor, genus Ruminococcaceae UCG009, and order Selenomonadales, whereas four groups of gut microbes can act as defense factors against HF, namely class Bacteroidia, genus Anaerostipes, order Bacillales, and order Bacteroidales.Huajie Dai 43 and others found that genus Eubacterium eligens group was causally associated with an increased risk of HF, which is consistent with our ndings.A previous study reported 44 that in pregnant women in pregnancy class Negativicutes abundance was signi cantly increased and causally associated with higher BMI in pregnant women, and a meta-analysis by Fatin Umirah et al 45 found a moderate to strong signi cant positive correlation between class Negativicutes and IL-6, and in addition, MR analysis by Feihong Ren et al 46 further showed a causal relationship between elevated class Negativicutes abundance and higher CRP levels. Multiple MR analyses 47,48 showed that genus Eubacterium eligens group increased the risk of CKD, in addition to a causal relationship with visceral adipose tissue (VAT) accumulation.Weiheng Yan et al 49 found that genus Ruminococcaceae UCG009 was associated with an OSA associated with an increased risk of morbidity. Taken together, our ndings suggest that targeting gut microbes that increase the risk of HF may be a promising strategy for the prevention of HF in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that out of 211 classes of gut microbiota, 6 classes of gut microbes were causally associated with increased risk of HF, namely genus Eubacterium eligens group, class Negativicutes, genus Eubacterium oxidoreducens group, genus Flavonifractor, genus Ruminococcaceae UCG009, and order Selenomonadales, whereas four groups of gut microbes can act as defense factors against HF, namely class Bacteroidia, genus Anaerostipes, order Bacillales, and order Bacteroidales.Huajie Dai 43 and others found that genus Eubacterium eligens group was causally associated with an increased risk of HF, which is consistent with our ndings.A previous study reported 44 that in pregnant women in pregnancy class Negativicutes abundance was signi cantly increased and causally associated with higher BMI in pregnant women, and a meta-analysis by Fatin Umirah et al 45 found a moderate to strong signi cant positive correlation between class Negativicutes and IL-6, and in addition, MR analysis by Feihong Ren et al 46 further showed a causal relationship between elevated class Negativicutes abundance and higher CRP levels. Multiple MR analyses 47,48 showed that genus Eubacterium eligens group increased the risk of CKD, in addition to a causal relationship with visceral adipose tissue (VAT) accumulation.Weiheng Yan et al 49 found that genus Ruminococcaceae UCG009 was associated with an OSA associated with an increased risk of morbidity. Taken together, our ndings suggest that targeting gut microbes that increase the risk of HF may be a promising strategy for the prevention of HF in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the genus Enterorhabdus has been negatively correlated with IL-10 and IL-4 inflammation factors [ 54 ], while the genus Butyricicoccus has been positively correlated with eGFR [ 55 ]. In a Mendelian randomization study, the genus Senegalimassilia was found relevant in the context of CKD [ 56 ]. Further, a species of the genus Haemophilus displayed an increased trend in CKD compared to Non-CKD participants [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, based on previous research experience 20 , we selected SNPs strongly associated with the risk factor using a signi cance threshold of P < 1x10 − 5 for analysis. Secondly, to avoid violating assumption one, we calculated the F-statistic for each SNP, de ning SNPs with F-statistic < 10 as weak instrumental variables and removing them 21 .To ensure that the impact of linkage disequilibrium (LD) was eliminated, an LD coe cient (r 2 ) threshold of 0.001 and a genetic distance of 10,000 kb were applied to remove SNPs in LD.…”
Section: Instrumental Variable Selectionmentioning
confidence: 99%